Simulation studies of nodular iron's bull's eye effect on stress concentration under plane stress conditions (2007)
A simulation study on the effect of the "bull's eye" in ductile iron on stress concerntrations was done in this work. Using the model of graphite nodules in a cavity, a two dimensional plate strip was subjected to plane stress conditions. The results were compared to to the traditonal theory of modeling the graphite in the hole model showed the hole matrix. In plane stress condition, while the graphite in the hole model showed the hole as areas of stress concerntration and therefore very critical as regards fracture, the hole model showed stress concentrated away from the holes making the holes not very critical factor as regards fracture. It was observed that areas of stress application were more critical than voids when using the hole model. Also the graphite in the hole model was able to predict the good damping behaviour of ductile iron and the increasing elongation with decreasing nodule count.